Implementasi Kebijakan Program Bantuan Pangan Non Tunai Di Desa Karyasari Kecamatan Banyuresmi Kabupaten Garut - Lia Juliasih; Siti Sovi Kustiara; Rostiena Pasciana (Program Studi Administrasi Negara Universitas Serang Raya, 2023)
Non-Cash Food Assistance (BPNT) is a type of social food assistance provided by the government to Beneficiary Families. BPNT distribution is done to alleviate poverty. The purpose of this study is to explain the execution of the non-cash food assistance program policy and to examine the supporting and inhibiting elements for the policy's implementation in Karyasari Village, Banyuresmi District, Garut Regency. This study employs qualitative research methodologies, which are evaluated in terms of process, results, and policy implications. The Non-Cash Food Assistance strategy has been implemented successfully in Karyasari Village. This is seen in the execution of proper policy standards and targets, resources that support aid distribution, communication across organizations, and implementing agents that understand field conditions. A robust communication mechanism, dependable human resources, and coordination among involved parties are factors that enable the operation of the Non-Cash Food Assistance policy. However, there are still obstacles impeding the execution of the Non-Cash Food Assistance program, such as beneficiaries of help who are not on target and information that is not well received due to the individuals receiving aid's low education.